Anatomical evaluation of the esophagus using computed tomography to predict acute gastroparesis following atrial fibrillation ablation. Issue 5 (28th August 2021) - Yakabe, Daisuke; Fukuyama, Yusuke; Araki, Masahiro; Nakamura, Toshihiro
Abstract: Background: Catheter ablation for atrial fibrillation is an effective treatment; however, periesophageal vagal nerve injury is not rare and sometimes results in acute gastroparesis (AGP) after atrial fibrillation ablation (AFA). We sought to investigate the incidence and risk factors of AGP via preprocedural computed tomography (CT) analysis. Methods: We retrospectively reviewed 422 patients who underwent index AFA at our center. Using contrast‐enhanced CT performed before ablation, the anatomical characteristics of the esophagus were compared between patients with and without post‐ablation AGP. AGP was diagnosed by the presence of symptoms, fasting abdominal X‐ray radiography as a screening test, and additional abdominal imaging. Results: Of the 422 patients (age, 67 ± 11 years; male, 68.5%; cryoballoon, 63.7%), AGP developed in 14 (3.3%) patients, and six of 14 patients were asymptomatic. AGP resolved in all patients within 4 weeks without invasive treatment. In the AGP group, the esophagus was frequently located on the vertebra (middle‐positioned esophagus) (AGP vs non‐AGP, 42.9% vs 11.5%; P  = .01), and additional posterior wall ablation was frequently performed (50.0% vs 14.5%; P  = .02). In the multivariate analysis, middle‐positioned esophagus ( P  = .02; odds ratio, 9.0; 95% confidence interval [CI], 1.5‐53.3) and additional posterior wall ablation ( P  = .01; odds ratio, 7.6; 95% CI, 1.5‐42.1) were independent predictors of AGP. Conclusions: Anatomical evaluation of the esophagus using CT may be simple and useful for predicting AGP after AFA. High‐risk patients who have middle‐positioned esophagus or who underwent excessive posterior wall ablation should be followed up closely. Abstract : This study revealed that 3.3% of patients following index atrial fibrillation ablation had acute gastroparesis (AGP) using rigorous screening tests after ablation. Middle‐positioned esophagus and posterior wall ablation were risk factors of AGP.